Hydrological Analysis of Loess Plateau Highland Control Schemes in Dongzhi Plateau - Huo, Aidi; Peng, Jianbing; Cheng, Yuxiang; Luo, Pingping; Zhao, Zhixin; Zheng, Chunli (Frontiers in Earth Science, 2020)
Gully Consolidation and Highland Protection Project (GCHP) is a major soil and water conservation and land remediation project implemented in the Chinese Loess Plateau (CLP). However, due to the lack of linking up between erosion mechanism and practical application, the implementation of these engineering measures is insufficient. Field investigation and descriptive statistics, together with hydrological analysis modeling were used in this study to gain an understanding of the impacts of Loess Plateau Highland Control Schemes (GCHP) on evolution for Dongzhi Plateau (the largest, most well-preserved and the thickest loess deposit region). A remote sensing image was introduced in hydrological modeling to prove the rationality of the hydrological analysis results in the Dongzhi Plateau. According to the investigations and analysis, the 4 major schemes of gully head retrogressive erosion control was summarized and a comprehensive theory and technology based on a watershed were proposed. After hydrological analysis, Dongzhi Plateau was divided into 1225 watersheds. It was found that GCHP should be implemented in the catchment area based on hydrological analysis to solve the fundamental problem of retrogressive erosion, and it is recommended to establish a scientific and rational drainage system based on roads and pipe networks in the whole watershed area. Findings from this paper can provide insight into the evolution of CLP and can help contribute to better management of a valuable GHCP.